Oral health–related quality of life in head and neck cancer: a systematic review - Piyarathne, Nadisha; Sinclair, Serena; Elsayed, Khaled Shawki; Cook, Chelsea; Gupta, Ekta; Abu-Eid, Rasha (Frontiers in Oral Health, 2025)
ObjectivesHead and Neck Cancer (HNC) is a devastating disease with significant mortality and morbidity. Patients suffer from compromised quality of life, due to the impact of the disease and its treatment on oral health and related functions. The aim of this systematic review was to identify the effects of HNC on oral health related quality of life (OHQoL).MethodsThe protocol followed PRISMA-2020 guidelines. Literature search was conducted in electronic databases (PSYC-INFO, EMBASE, OVID-MEDLINE, SCOPUS, and WEB OF SCIENCE) at three time points, yielding 1198 records. Abstracts and full-texts were screened, and 101 eligible articles were identified. The risk of bias assessment was conducted using Joanna Briggs Institute critical appraisal tools. Narrative data synthesis was conducted under broad themes that influenced OHQoL; patient factors, diagnosis and treatment, and post treatment.ResultsStudies were published between 2001 and 2024, a growing interest in OHQoL research was noted over time. 70.3% of the studies used oral health impact profile (OHIP-14) for OHQoL assessment. Among patient factors, low socioeconomic status, being without a partner and underweight were associated with worse scores. OHQoL varied with anatomical location of HNC, treatment modalities and their side effects such as mucositis and xerostomia. Prosthetic rehabilitation positively influenced OHQoL post-treatment.ConclusionsOHQoL assessment is critical in HNC patients from diagnosis, during treatment and beyond. It is influenced by factors related to sociodemographic, diagnosis, treatment, reconstruction and rehabilitation. The findings of this study can inform and guide clinicians to update supportive care and existing management of HNC and OPMD patients.